Unveiling Firm Value: Exploring Price to Book Value Method in Nigerian Food and Beverage Companies - Akpor, Afam Augustine; Ogbaini, Clement Aliu; Oboh, Ransome; Oputa, John Edewor; Bello-Marvis, Vine; Okafor, Ndubuisi (Neraca: Jurnal Pendidikan Ekonomi, 2024)
This study examined the effect of asset effectiveness, profitability, leverage, liquidity, and company size on firm value in the Food and Beverage companies that are listed on the Nigerian Stock Exchange. The study employed the descriptive research design method, and purposive sampling techniques were used to select 10 out of 23 food and beverage companies listed in the Nigerian Stock. Secondary data was collected from the five-year financial statements of the companies. The study adopted E-views 12 to analyze all the data in this study. The finding of this study revealed that Current Asset (CR) has a negative and insignificant effect on food and beverages firms’ PBV, Debt-Equity Ratio (DER) has a positive and significant impact on PBV, Return on Asset (ROE) has a positive and an insignificant impact on PBV and Company Size (CS) has a negative and a significant impact on PBV. The study recommends that; firms must strike a balance between liquidity and efficiency to maximize firm value. Companies should aim to strike a balance between debt and equity that aligns with their strategic objectives and risk tolerance. Companies should regularly review and adjust their DER ratios as part of their overall financial strategy. Investors and analysts should adopt a comprehensive approach to evaluating firm value.